Educational Development in Khyber Pakhtunkhwa (N.W.F.P): An Historical Perspective - Asadullah; Attaullah; Ali, Niaz (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper investigates the overall educational conditions of Khyber Pakhtunkhwa during the British rule, and also explore the prevailing educational system in the province. It further explain the deplorable educational conditions of the Muslims on the eve of British arrival in the province of Khyber Pakhtunkhwa. After the occupation of the province and introduction of modern education by the Britishers, various educational movements in reaction were initiated by some prominent religious, social and political elites. These educational movements are thoroughly investigated in the research paper.